Absorptive capacity, resources and alliances: Does technology transfer lead to enhanced manufacturing performance? - Jabar, Juhaini; Soosay, Claudine (2012)
This study investigates the performance of Malaysian manufacturers based on strategic technology alliances formed with other organisations and the mediating effect of technology transfer. Data were collected from 335 firms and analysed using structural equation modelling. Our findings indicate that the absorptive capacity of firms and type of alliances formed are factors which instigate the alliance formation and resulting technology transfer. However, this transfer of technology only partially mediates the relationship between the alliance and organisational performance. This provides practical implications for managers to consider various aspects including technology uncertainty levels and inter-organizational relations in order for Malaysian manufacturers to achieve superior manufacturing performance.